A CRITICAL ANALYSIS ON IMPLEMENTATION ON SENIOR CITIZEN ACT-2007 WITH SPECIAL REFERENCE OF AHMEDABAD DISTRICT - Jani, Bhoomika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Ahmedabad District is the subject of a particular analysis in this paper's critical examination of the Maintenance and Welfare of Parents and Senior Citizens Act, 2007. The Act requires adult children and legal heirs to take care of their aging parents to offer financial and social security to senior folks. The practical implementation of this law presents several obstacles despite its well-intentioned goals, especially in varied socioeconomic and cultural environments such as Ahmedabad. This assessment evaluates how well the Act's provisions protect the welfare and rights of elderly residents by examining the functions of regional law enforcement, courts, and public awareness campaigns. The study used a mixed-methods approach, integrating qualitative interviews with Ahmedabad's social workers, law enforcement officers, and elderly residents with quantitative data from tribunal case records. Important discoveries show a discrepancy between the theoretical foundation of the legislation and its practical implementation, characterized by low knowledge, restricted access to legal remedies, and inadequate support networks for the aged.